Design and Implementation of Laboratory Equipment Information System: A Case Study at SMK 1 Sigli - Riza, Muhammad (Journal Dekstop Application (JDA), 2024)
This research discusses the design and implementation of an information system for laboratory equipment management at SMK 1 Sigli, specifically in the Fashion Design department. Manual management of laboratory equipment often leads to inefficiencies and errors in data recording. To address these issues, a computer-based system was developed using Microsoft Visual Basic and Microsoft Access, replacing the previously used Microsoft Excel-based system. The system automates several processes, such as data entry, equipment tracking, and report generation, improving operational efficiency. A needs analysis was conducted with laboratory managers to ensure the system design met the operational requirements. The development process included creating a user-friendly interface and an organized database structure. As a result, the system enables real-time monitoring of equipment, reduces errors, and speeds up decision-making related to maintenance and procurement. Feedback from laboratory staff indicates that the system successfully improves the accuracy and efficiency of equipment management. This research provides a practical solution that can be applied to other schools facing similar challenges in laboratory resource management.